UNDERSTANDING BETTER THE KNOWLEDGE, BELIEFS, AND ATTITUDES TOWARD BREAST CANCER AND BREAST SCREENING PRACTICES AMONG WOMEN LIVING IN RAS AL KHAIMAH, UNITED ARAB EMIRATES (UAE) (Proceedings of the International Conference on Public Health, 2017)
Breast cancer is the most frequently diagnosed malignant disease among women in the United Arab Emirates (UAE), and the incidence rate is rising. Breast cancer early detection practices through regular screening have been found to reduce morbidity and mortality from this disease. This study aims to explore the knowledge, beliefs, attitudes, and practices towards breast cancer and its screening methods among women living in the emirate of Ras Al Khaimah (RAK). One hundred and two women who met the study’s inclusion criteria were interviewed. Pearson’s chi-squared test and multivariate logistic regression analysis were performed in the statistical analysis. Relatively low participation rates in breast cancer screening practices (BCSP) were found. Women who stated that their doctors talked to them about breast cancer were significantly more likely to undergo BCSP (p
Keywords: Breast cancer screening practices; Breast Self-Examination; Clinical Breast Examination; Mammography